2017
DOI: 10.1016/j.niox.2017.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Disparate response to microoxia and nitrogen oxides of the Bradyrhizobium japonicum napEDABC, nirK and norCBQD denitrification genes

Abstract: Manuscript number NOX_2016_125Title Disparate response to microoxia and nitrogen oxides of the Bradyrhizobium japonicum napEDABC, nirK, and norCBQD denitrification genes Article type Research Paper AbstractExpression of the Bradyrhizobium japonicum napEDABC, nirK and norCBQD denitrification genes requires low oxygen (O2) tension and nitrate (NO3-), through a regulatory network comprised of two coordinated cascades, FixLJ-FixK2-NnrR and RegSR/NifA. To precisely understand how these signals are integrated in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
58
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(65 citation statements)
references
References 74 publications
7
58
0
Order By: Relevance
“…Previous work by other groups showed that transcription of denitrification genes in the model organism Bradyrhizobium diazoefficiens USDA 110 (earlier called B. japonicum) is regulated by the O 2 sensitive FixJL, the NO 3 − -sensitive NasTS, the NO sensitive NnrR, the redox sensitive RegSR and the RegR and self-induced NifA (Torres et al, 2014;Cabrera et al, 2016). Noticeably, the expression of the nap and nir operons was apparently initiated by microoxic conditions, while that of the nor operon required a nitrogen oxide, probably NO (Bueno et al, 2017). Regulation of nosZ was not investigated, but another study (Torres et al, 2017) suggested microaerobic conditions as the main inducer of nosZ.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work by other groups showed that transcription of denitrification genes in the model organism Bradyrhizobium diazoefficiens USDA 110 (earlier called B. japonicum) is regulated by the O 2 sensitive FixJL, the NO 3 − -sensitive NasTS, the NO sensitive NnrR, the redox sensitive RegSR and the RegR and self-induced NifA (Torres et al, 2014;Cabrera et al, 2016). Noticeably, the expression of the nap and nir operons was apparently initiated by microoxic conditions, while that of the nor operon required a nitrogen oxide, probably NO (Bueno et al, 2017). Regulation of nosZ was not investigated, but another study (Torres et al, 2017) suggested microaerobic conditions as the main inducer of nosZ.…”
Section: Discussionmentioning
confidence: 99%
“…Nar is composed of 3 subunits encoded by narGHI, as found in E. coli, P. fluorescens, P. stutzeri and B. subtilis (Philippot and Højberg, 1999;Lalucat et al, 2006), whereas Nap is composed of 2 subunits encoded by napAB, as found in Rhodabacter sphaeroides and B. japonicum (Reyes et al, 1998;Bedmar et al, 2005). The nar operon is induced under low oxygen partial pressure and in the presence of nitrogen oxides (Philippot et al, 2001;Giannopoulos et al, 2017), whereas the expression of the nap operon can be affected or not by anaerobiosis depending on the organism (Philippot, 2002;Bueno et al, 2017).…”
Section: Denitrificationmentioning
confidence: 99%
“…Expression of B. diazoefficiens denitrification genes required low oxygen tension and in the case of norCBQD genes the presence of NO is also needed ( Bueno et al, 2017 ). In this bacterium, perception and transduction of the ‘low-oxygen’ signal are mediated by a complex network comprising two interconnected regulatory cascades, the FixLJ–FixK 2 –NnrR and the RegSR–NifA ( Sciotti et al, 2003 ).…”
Section: Introductionmentioning
confidence: 99%